Career aspirations of Malaysian research and development professionals in the knowledge economy - Ismail, Maimunah; Ramly, Efizah Sofiah (Emerald Group Publishing, 2011)
Purpose: This paper seeks to compare the influence of self‐efficacy, organizational socialization and continuous improvement (CI) practices on the career aspirations of research and development (R&D) professionals in government research institutes (GRIs) and multinational corporations (MNCs) in Malaysia. R&D professionals in this study refer to a specific group of knowledge workers. Design/methodology/approach: Social cognitive career theory (SCCT) was used as this study's theoretical framework. The study involved 164 respondents from GRIs and 120 respondents from MNCs in Malaysia. Descriptive statistics and inferential multiple linear regressions were used to analyse the data. Findings: Self‐efficacy and organizational socialization were found to differ significantly in terms of their levels, and CI practices and career aspirations were not found to be significantly different between the two groups of respondents. Regression results showed MNCs reported higher explanatory power compared to that of the GRIs in terms of the variance in career aspirations. Research limitations/implications: The insights generated about the factors affecting career aspirations are based on three independent variables, namely: self‐efficacy, organizational socialization and CI practices that are most suitable for a R&D environment. Practical implications: This study confirms the relevance of CI practices in the existing model of SCCT because it represents the organizational variables. HRD practitioners in both types of organizations should consider changing the work practices of R&D professionals by strengthening the quality improvement procedures because they affect the professionals' career aspirations. Originality/value: Incorporating CI practices into the SCCT model is believed to be a contribution of this study to the theory.